Front Cover: NiMo‐Ceria‐Zirconia Catalyst for Inert‐Substrate‐Supported Tubular Solid Oxide Fuel Cells Running on Model Gasoline (Energy Technol. 1/2019). Issue 1 (22nd January 2019) - Zhao, Kai; Bkour, Qusay; Kim, Bok‐Hee; Norton, M. Grant; Ha, Su
Abstract : Heterogenous Catalysis in Fuel Cells : A liquid‐fuel solid oxide fuel cell is successfully demonstrated for its potential transportation applications. By applying a novel NiMo‐ceria‐zirconia reforming catalyst in the tubular cell, logistic fuels can be efficiently reformed into synthesis gas before electrochemical oxidation. The internal reforming unit acts as a fuel‐cleaning filter, which significantly suppresses coking and improves the cell lifetime. More details can be found in the Communication by Kai Zhao et al. onpage 48 in Issue 1, 2019 (10.1002/ente.201700843 ).